Aberrant plasma IL-7 and soluble IL-7 receptor levels indicate impaired T-cell response to IL-7 in human tuberculosis - Lundtoft Christian; Nausch Norman; Owusu-Dabo Ellis; Jacobsen Marc; Lang Franziska....et al (PLOS, 2023)
This article is published by Plos and is also available at https://doi.org/10.1371/journal.ppat.1006425